Prolonged Postoperative Opioid Use After Arthroscopic Femoroacetabular Impingement Syndrome Surgery: Predictors and Outcomes at Minimum 2-Year Follow-up. Issue 11 (29th November 2021) - Beck, Edward C.; Nwachukwu, Benedict U.; Drager, Justin; Jan, Kyleen; Rasio, Jonathan; Krishnamoorthy, Vignesh P.; Nho, Shane J.
Background: The association between prolonged postoperative opioid use on outcomes after hip preservation surgery is not known. Purpose: To compare minimum 2-year patient-reported outcomes (PROs) between patients who required ≥1 postoperative opioid refill after undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS) versus patients who did not require a refill and to identify preoperative predictors for patients requiring ≥1 postoperative opioid refill. Study Design: Cohort study; Level of evidence, 3. Methods: Data from consecutive patients who underwent arthroscopic surgery for FAIS between January 2012 and January 2017 were analyzed. Multivariate regression analysis was performed to classify patient and radiographic variables as predictive of requiring ≥1 opioid prescription refill after surgery. Patients completed the following PROs preoperatively and at 2-year follow-up: Hip Outcome Score— Activities of Daily Living subscale (HOS-ADL), HOS–Sports Subscale (HOS-SS), modified Harris Hip Score (mHHS), International Hip Outcome Tool (iHOT-12), and 100-point visual analog scale (VAS) for pain and satisfaction. Scores were compared between patients needing additional prescription opioids and those who did not. Results: A total of 775 patients, of whom 141 (18.2%) required ≥1 opioid prescription refill, were included in the analysis. Patients requiring opioid refills had significantly lower 2-year postoperative PRO scores compared with patients not requiring refills: HOS-ADL (79.9 ± 20.3 vs 88.7 ± 14.9), HOS-SS (64.6 ± 29.5 vs 78.2 ± 23.7), mHHS (74.2 ± 21.1 vs 83.6 ± 15.9), iHOT-12 (63.6 ± 27.9 vs 74.9 ± 24.8), and VAS satisfaction (73.4 ± 30.3 vs 82.2 ± 24.9), as well as significantly more pain (26.8 ± 23.4 vs 17.9 ± 21.8) ( P ≤ .001 for all). Predictors of requiring a postoperative opioid refill included patients with active preoperative opioid use (odds ratio, 3.12 [95% confidence interval, 1.06-9.21]; P = .039) and larger preoperative alpha angles (odds ratio, 1.04 [95% confidence interval, 1.01-1.07]; P = .03). Conclusion: Patients requiring ≥1 opioid prescription refill after hip arthroscopy for FAIS had lower preoperative and 2-year PRO scores when compared with patients not requiring refills. Additionally, active opioid use at the time of surgery was found to be predictive of requiring additional opioids for pain management.